NIDIFICACIÓN, CONDUCTA DE MACHOS DE CENTRIS (WAGENKNECHTIA) RODOPHTHALMA PÉREZ (HYMENOPTERA: ANTHOPHORIDAE) Y COMPARACIÓN CON OTRAS ESPECIES CHILENAS DEL GÉNERO - Chiappa T., Elizabeth; Bascuñán, Rossana; Rodríguez, S. (Acta Entomológica Chilena, 2022)
The nesting biology of Centris rodophthalma Pérez is described and compared lo published accounts of C. autrani, C. cineraria, C. mixta tamarugalis and C. nigerrima. All are ground nesting solitary species with nests constructed in plañe surfaces or soft slopes, but those of C. cineraria and C. nigerrima are located into vertical walls too. Except C. mixta tamarugalis, the other ones, built a not ramified tunnel filled with loose soil when the nests have been closcd. The number and disposition of the cells is different in each one of the species, no more than 10 serially arranged in C. autrani, 3-4 placed laterally in C. cineraria and C. nigerrima, 4-8 in C. mixta tamarugalis near the tunnel base, and 1-3 radially distributed at the end of a not curved tunnel in C. rodophthalma. In addition, proterandry, mating, male mating strategies, sleeping aggregations as well as rejection of males by fcmales are reported and discusssed.